Cloud computing security: a survey - Sheela Gowr, P; Kumar, N (International Journal of Engineering and Technology, 2018)
Cloud computing was a hasting expertise which has innovated to a collection of new explores. A sub-ordinate device for Information services, it has an ability towards encourage development by feeding convenient environments for a choice of forms of development is different sequence. Clouds usually consider being eco-friendly, however keep it has open to the diversity of some security issues to can change together the feeder as well as users of these cloud services. In this issue are principally associated to the protection of the information flow throughout also being store in the cloud, with simple problems along with data ease of use, data right to use and data confidentiality. Data encryption and service authentication scheme has been initiated by the industries to deal with them. In this paper analyse and examine different issues on security beside with the different procedure worn by the industries to solve these effects.Â